2017
DOI: 10.1186/s40816-017-0049-4
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of black tea on human cognitive performance in a cognitive test battery

Abstract: Background: Black Tea is a widely consumed drink in the world. Evidence suggest Black Tea has stimulatory effect on humans. We investigated the effect of Black Tea on cognition using a cognitive test battery. Methods: Participants (n = 32) were fasted overnight for 10 h and restrained from caffeine and other stimulant drugs for 14 days prior to participation. We randomly assigned participants into either an experimental (n = 16) or a control (n = 16) group. Experimental group consumed 250 ml of Black Tea (BT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Further caffeine consumption can improve vigilance performance and reaction time [45]. Functional magnetic resonance imaging (fMRI) has been used to look at the effects of caffeine on cognition [46]. One study reported that caffeine alters neuronal activity in the dorsolateral prefrontal cortex (DLPFC) during working memory tasks [47].…”
Section: Discussionmentioning
confidence: 99%
“…Further caffeine consumption can improve vigilance performance and reaction time [45]. Functional magnetic resonance imaging (fMRI) has been used to look at the effects of caffeine on cognition [46]. One study reported that caffeine alters neuronal activity in the dorsolateral prefrontal cortex (DLPFC) during working memory tasks [47].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that characteristic oxidized polyphenols (e.g., thearubigins and theaflavins) in black tea may have a distinct effect. However, regular consumption of black or green tea have both been shown to reduce the risk of neurocognitive disorders 46 errors, and speed up performance of subjects in a variety of cognitive tasks compared to consumption of a water control 52 , although the study did not differentiate if the effects were due to caffeine or tea polyphenol content.…”
Section: Tea and Brain Healthmentioning
confidence: 93%
“…Black tea (Camellia sinensis L.) is the most consumed kind of tea worldwide . A series of studies have reported the antiaging role of black tea. Theaflavins (TFs) are a mixture of four major ingredients formed from enzymatic oxidation of various catechins in the process of fermentation during the manufacture of black tea: theaflavin (TF1), theaflavin-3-gallate (TF2A), theaflavin-3′-gallate (TF2B), and theaflavin-3,3′-digallate (TF3) . Even though TFs are in low content and usually account for 0.3–2% of the dry mass of black tea leaves, they are responsible for the positive qualities of tea, such as the characteristic reddish color and astringency.…”
Section: Introductionmentioning
confidence: 99%